Duration of respiratory events in obstructive sleep apnea: Factors influencing the duration of respiratory events. (April 2023) - Oksenberg, Arie; Leppänen, Timo
Abstract: Several factors influence respiratory event duration during sleep. In general, women have shorter respiratory events compared to men as it appears that women have a more reactive upper airway contributing to the occurrence of short events. In addition, the increased amount of adipose tissue in the upper airways should make the reopening of the upper airways more difficult, leading to long respiratory events. Nevertheless, an increase in body mass index decreases the median duration of apneas, hypopneas, and desaturations in all OSA severity categories. Also, respiratory events are longer in older adults compared to younger ones, and the most likely mechanism explaining this phenomenon appears to be the increased circulatory delay associated with aging. Several studies have also shown that apnea events are longer in rapid eye movement sleep compared to non-rapid eye movement sleep. The main mechanism behind these differences appears to be the greater pharyngeal muscle relaxation during rapid eye movement sleep. Finally, sleeping position affects the duration of respiratory events; apneas and hypopneas are longer in the supine compared to lateral postures regardless of the severity of OSA. In the present report, we discuss the best-known factors influencing the duration of abnormal breathing events during sleep.